The Role of Distributed Leadership In Improving Work Environment Conditions Through the Mediating Role of Innovation Readiness: an Applied Study - Israa Oleiwi (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
The study aims to explore the role of distributed leadership (DIL) among employees in private hospitals in improving work environment conditions (WEC) through innovation readiness. This objective was established to address a significant problem, namely: (Is there a role for DIL in improving WEC through the mediating role of innovation readiness among employees in private hospitals?). To tackle this problem, a descriptive-analytical approach was adopted using a questionnaire as the tool for data collection. Accordingly, 100 questionnaires were distributed, 79 were retrieved, 66 of which were valid and 13 were invalid. For the purpose of data analysis, the SPSS & AMOS package was employed to determine the levels of the study variables. Accordingly, the study produced several results, foremost of which is the existence of a correlation between DIL, WEC, and Innovation Readiness. This indicates that Innovation Readiness contributes to enhancing the relationship between DIL and WEC, highlighting the prioritisation of private hospitals on improving these variables through enhancing openness to innovation and flexibility of administration among employees. This leads to building supportive functional and supervisory quality, participation in informed decision-making, which improves collaboration within work teams, directly reflecting on creating a behavioural and material work environment aimed at achieving the organisation's long-term vision. The study also offered several recommendations, the most important of which focused on the necessity of continuously developing employees’ capabilities by encouraging them to participate in ongoing training courses to enhance their skills and Innovation abilities, thereby improving working and organisational conditions in hospitals and providing greater opportunities for employee development and utilising their capabilities in a manner that serves the organisation's objectives..